Incidence and Characterization of Rectal Complications From Fecal Management Systems. Issue 1 (January 2022) - Kane, William J.; Hassinger, Taryn E.; Xu, Thomas O.; Kirkner, Allison E.; Maddox, Michele J.; Hoang, Sook C.; Friel, Charles M.; Hedrick, Traci L.
Abstract : BACKGROUND: Fecal management systems have become ubiquitous in hospitalized patients with fecal incontinence or severe diarrhea, especially in the setting of perianal wounds. Although fecal management system use has been shown to be safe and effective in initial series, case reports of rectal ulceration and severe bleeding have been reported, with a relative paucity of clinical safety data in the literature. OBJECTIVE: The purpose of this study was to determine the rate of rectal complications attributable to fecal management systems, as well as to characterize possible risk factors and appropriate management strategies for such complications. DESIGN: This was a retrospective cohort study. SETTINGS: The study was conducted at a large academic medical center. PATIENTS: All medical and surgical patients who underwent fecal management system placement from December 2014 to March 2017 were included. MAIN OUTCOME MEASURES: We measured any rectal complication associated with fecal management system use, defined as any rectal injury identified after fecal management system use confirmed by lower endoscopy. RESULTS: A total of 629 patients were captured, with a median duration of fecal management system use of 4 days. Overall, 8 patients (1.3%) experienced a rectal injury associated with fecal management system use. All of the patients who experienced a rectal complication had severe underlying comorbidities, including 2 patients on dialysis, 1 patient with cirrhosis, and 3 patients with a recent history of emergent cardiac surgery. In 3 patients the bleeding resolved spontaneously, whereas the remaining 5 patients required intervention: transanal suture ligation (n = 2), endoscopic clip placement (n = 1), rectal packing (n = 1), and proctectomy in 1 patient with a history of pelvic radiotherapy. LIMITATIONS: The study was limited by its retrospective design and single institution. CONCLUSIONS: This is the largest study to date evaluating rectal complications from fecal management system use. Although rectal injury rates are low, they can lead to serious morbidity. Advanced age, severe comorbidities, pelvic radiotherapy, and anticoagulation status or coagulopathy are important factors to consider before fecal management system placement. See Video Abstract at http://links.lww.com/DCR/B698 . INCIDENCIA Y CARACTERIZACIÓN DE LAS COMPLICACIONES RECTALES DE LOS SISTEMAS DE MANEJO FECAL: ANTECEDENTES: Los sistemas de manejo fecal se han vuelto omnipresentes en pacientes hospitalizados con incontinencia fecal o diarrea severa, especialmente en el contexto de heridas perianales. Aunque se ha demostrado que el uso del sistema de tratamiento fecal es seguro y eficaz en la serie inicial, se han notificado casos de ulceración rectal y hemorragia grave, con una relativa escasez de datos de seguridad clínica en la literatura. OBJETIVO: Determinar la tasa de complicaciones rectales atribuibles a los sistemas de manejo fecal. Caracterizar los posibles factores de riesgo y las estrategias de manejo adecuadas para tales complicaciones. DISEÑO: Estudio de cohorte retrospectivo. ENTORNO CLINICO: Centro médico académico de mayor volumen. PACIENTES: Todos los pacientes médicos y quirúrgicos que se sometieron a la colocación del sistema de manejo fecal desde diciembre de 2014 hasta marzo de 2017. PRINCIPALES MEDIDAS DE VALORACION: Cualquier complicación rectal asociada con el uso del sistema de manejo fecal, definida como cualquier lesión rectal identificada después del uso del sistema de manejo fecal confirmada por endoscopia baja. RESULTADOS: Se identificaron un total de 629 pacientes, con una duración media del uso del sistema de manejo fecal de 4, 0 días. En general, 8 (1, 3%) pacientes desarrollaron una lesión rectal asociada con el uso del sistema de manejo fecal. Todos los pacientes que mostraron una complicación rectal tenían comorbilidades subyacentes graves, incluidos dos pacientes en diálisis, un paciente con cirrosis y tres pacientes con antecedentes recientes de cirugía cardíaca emergente. En tres pacientes el sangrado se resolvió espontáneamente, mientras que los cinco pacientes restantes requirieron intervención: ligadura de sutura transanal (2), colocación de clip endoscópico (1), taponamiento rectal (1) y proctectomía en un paciente con antecedentes de radioterapia pélvica. LIMITACIONES: Diseño retrospectivo, institución única. CONCLUSIONES: Este es el estudio más grande hasta la fecha que evalúa las complicaciones rectales del uso del sistema de manejo fecal. Si bien las tasas de lesión rectal son bajas, pueden provocar una morbilidad grave. La edad avanzada, las comorbilidades graves, la radioterapia pélvica y el estado de anticoagulación o coagulopatía son factores importantes a considerar antes de la colocación del sistema de manejo fecal. Consulte Video Resumen en http://links.lww.com/DCR/B698 . Abstract : Supplemental Digital Content is available in the text.